2021
DOI: 10.3389/fchem.2021.724188
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanomaterials and Bone/Cartilage Tissue Engineering: Biomedical Applications and Molecular Mechanisms

Abstract: Recently, as our population increasingly ages with more pressure on bone and cartilage diseases, bone/cartilage tissue engineering (TE) have emerged as a potential alternative therapeutic technique accompanied by the rapid development of materials science and engineering. The key part to fulfill the goal of reconstructing impaired or damaged tissues lies in the rational design and synthesis of therapeutic agents in TE. Gold nanomaterials, especially gold nanoparticles (AuNPs), have shown the fascinating feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…On the other hand, nanogold (13 nm, 10 μg) could inhibit the mechanism of RA by binding to VEGF and inhibiting the proliferation and migration of endothelial cells. AuNPs (13 or 50 nm; 3.76 μg) can also inhibit ROS and prevent the destruction of RA synovitis [ 7 ]. Therefore, AuNPs can inhibit angiogenic activity, inhibit inflammation, or act as antioxidants, to protect cartilage tissue in arthritis.…”
Section: Bone Cartilage Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, nanogold (13 nm, 10 μg) could inhibit the mechanism of RA by binding to VEGF and inhibiting the proliferation and migration of endothelial cells. AuNPs (13 or 50 nm; 3.76 μg) can also inhibit ROS and prevent the destruction of RA synovitis [ 7 ]. Therefore, AuNPs can inhibit angiogenic activity, inhibit inflammation, or act as antioxidants, to protect cartilage tissue in arthritis.…”
Section: Bone Cartilage Disordermentioning
confidence: 99%
“…Therefore, AuNPs can inhibit angiogenic activity, inhibit inflammation, or act as antioxidants, to protect cartilage tissue in arthritis. Studies have shown that AuNPs have the ability to inhibit osteoclasts and are one of the most effective nanoparticles for the treatment of bone tissue diseases [ 7 , 39 ].…”
Section: Bone Cartilage Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing fast and accurate hydrogen sensors is of great importance for safely using hydrogen energy. Hydrogen sensors based on various structures and mechanisms have been reported in the past decade, including micro-electro-mechanical systems, semiconductors, optical, , electrochemical, TE, , and other hybrid catalytic systems. TE hydrogen sensors (TEHs) attracted the attention of researchers for their high selectivity, fast response, low power consumption, and minimum maintenance requirements …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the more sensitive and collective biosensor is potential. Meanwhile, the nanomaterials are the most potential and hot one [1].…”
Section: Introductionmentioning
confidence: 99%